“I don’t Teach Violence, I Teach Self-Control”; The Framing of Mixed Martial Arts Between Mental Health and Well-Being - Domaneschi, Lorenzo; Ricci, Oscar (Frontiers in Sociology, 2022)
This paper draws on conceptual and analytical tools from cultural sociology to analyze media representations of the MMA right after the murder of a twenty-year-old boy, that took place in a small village in central Italy by a gang of young men, two of whom frequented a MMA gym. While often characterized as violent and uncivilized, MMA has a core following of fans who watch and practice MMA out of an interest in the effects of the sport in terms of health and well-being. Through in depth qualitative analysis of  MMA media discourse offered by traditional and new media, this paper explores the way the MMA media constructs symbolic boundaries around different kinds of fights inside and outside the gym, through aesthetic and moral evaluations based on the hierarchical ‘distinctions’ between “violence” and “health” as possible outcomes of the MMA training process. Particularly, we carry out a discourse analysis based on Italian Newspapers, Magazines and Facebook groups dedicated to MMA, through which we frame the multiple representations of the discursive production built around the MMA in Italy. Our aim is to identify the different ways in which the discussion about this event provided narrative paths and points of view about the meaning of MMA, focusing on the reputational consequences concerning health, especially in its physical and mental expressions. This research may prove useful for scholars interested in MMA, culture, and sports media studies.